Detection and research of acoustic emission effects at a plastic strain of steels in a magnetic field - Papirov, I.I.; Stoev, P.I. (Reports of the National Academy of Sciences of Ukraine, 2014)
The features of the behavior of the acoustic emission parameters during a plastic deformation of steels 3 and 1Kh18N9T in a magnetic field are studied. For the first time, new acoustic-emission effects which are induced by a magnetic field are found. In the case of steel 3, the application of a magnetic field in the process of deformation of the samples results in significant changes in the spectrum of the amplitudes of acoustic emission signals and the elimination of the yield "tooth". On the maximum of the acoustic emission activity in the field of strains corresponding to the beginning of flow of a metal, the magnetic field leads to the activation of smaller dislocation ensembles with low amplitudes and a substantial reduction of the role of large-size dislocation ensembles with high amplitude. The deformation in the magnetic field of austenitic steel 1Kh18N9T leads to the additional generation of acoustic signals, the formation of an inflection on the curve of the total sum of pulses associated with the α-martensitic transformation, and a significant change of the spectrum of acoustic emission signals at the test in a magnetic field and when the field is absent. The results indicate that the main cause of the influence of a magnetic field on the plastic deformation of the tested steels is not a change in the parameters of thermal activation of a plastic flow, but a significant restructuring of the dislocation ensembles participating in the process.